2022
DOI: 10.1136/bmjopen-2021-059084
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram for prediction of postoperative sore throat in patients under general anaesthesia: a single-centre, prospective, observational study

Abstract: ObjectivesPostoperative sore throat (POST) is very common in patients under general anaesthesia. However, there is no effective clinical predictive model for reducing its occurrence. The objective of this study was to estimate the risk factors for POST in patients after general anaesthesia by designing a nomogram.DesignA prospective study.SettingThis study was conducted in a large tertiary hospital.ParticipantsPatients aged 18–85 years old who received general anaesthesia with either an endotracheal tube or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There have been different results depending on the population studied and have found conflicting results. Some authors have found a higher incidence amongst young patients [2], and others claim the incidence is higher amongst geriatric patients [3]. It is well known that as we age, our nervous fibers become less sensitive to pain stimuli, so it is probable that the risk factor of old age is more associated to difficult airways that are common in geriatric patients, rather than old age itself.…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…There have been different results depending on the population studied and have found conflicting results. Some authors have found a higher incidence amongst young patients [2], and others claim the incidence is higher amongst geriatric patients [3]. It is well known that as we age, our nervous fibers become less sensitive to pain stimuli, so it is probable that the risk factor of old age is more associated to difficult airways that are common in geriatric patients, rather than old age itself.…”
Section: Agementioning
confidence: 99%
“…POST is importantly linked to the use of larger lumen endotracheal tubes (ETT). Many authors have found a lower incidence of POST when reducing the ETT size [2,3,5,6] even by 0.5 mm. Traditionally, larger ETT were selected to reduce airflow resistance and provide better ventilation, but this intervention has little significance when the ventilation is transitory as is in a surgical procedure.…”
Section: Endotracheal Tube Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Although POST is a minor complication, it reduces patient satisfaction and extends the hospital stay. [ 1 , 2 ] The incidence of POST ranges between 12.1% and 70%, depending on the study. [ 3 ] The etiology of POST involves damage to the airway mucosa due to endotracheal intubation under GA. [ 4 ] The symptoms of POST include pain, discomfort, hoarseness, and coughing.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic agent spray or gargle, steroids administration, are proposed to reduce the incidence of sore throat, but yield controversy on the efficacy of the treatments [ 2 , 6 , 7 ]. Except for local pharyngeal mucous injury, other risk factors such as age, surgical duration, gender were also involved in initiating POST after SAD insertion [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%